2022
DOI: 10.1007/s12134-022-00937-2
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Sociolinguistic Perspectives in Australian Refugee Credibility Assessments: the Case of CRL18

Abstract: Credibility assessments in asylum visa applications have attracted criticism across diverse research fields. This article builds on existing critical examinations by presenting a case study of a successful appeal in the Federal Court of Australia (FCA) which overturned a decision involving one such problematic credibility assessment. The article establishes that credibility assessments often rely on flawed language ideologies and reasoning that transform the asylum seeker into the sole participant responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The university discourses in our data reinforce precisely that association by subjugating a group of applicants who numerically are mostly Asian to the objectivized scrutiny of language testing while exempting others. In the process, it is not only the perception of the ELP of this group that is called into question but also their credibility and moral worth (Piller et al 2021; Smith-Khan 2019, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The university discourses in our data reinforce precisely that association by subjugating a group of applicants who numerically are mostly Asian to the objectivized scrutiny of language testing while exempting others. In the process, it is not only the perception of the ELP of this group that is called into question but also their credibility and moral worth (Piller et al 2021; Smith-Khan 2019, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Sociolinguists have found credibility assessments in asylum determinations to rest on problematic language ideologies, including a belief that oral communication is detached from social categorizations and institutional discourses (Barsky, 1994;Smith-Khan, 2022). Moreover, sociolinguists exploring the interaction between decision-makers, asylum seekers, interpreters, and lawyers during asylum interviews have revealed that asylum narratives are co-constructed by all participants and influenced by the asymmetrical power relations between the professional workers and the applicants (Blommaert, 2001;Maryns, 2006;Määttä, Puumala & Ylikomi, 2021;Jacobs & Maryns, 2021;.…”
Section: Contested Assumptions Underpinning Credibility Assessmentsmentioning
confidence: 99%